Reversible addition fragmentation chain transfer (RAFT) mediated polymerization of N-vinylpyrrolidone - Pound, Gwenaelle (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Chemistry and Polymer Science)--University of Stellenbosch, 2008.